Abundance distribution gastropods telescopium telescopium Mangrove ecosystem in river estuary dumai - Bonawi Sihombing; Syafruddin Nasution; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in December 2013 at Dumai river estuary. Thestudy aims were to determine the abundance distribution of mangrove snail (T.telescopium) and correlation between abundance and sediment organic content.The method used was a survey method. Samples of snail population and sedimentwere collected by a single visit during low tide. Location of study was dividedinto 3 stations. Station I located inside the conservation area, station II waslocated close to shipyard, while station III laid near by a residential community.The analysis carried out in Marine Biologi Laboratory of Riau University.The results of the study show that the highest abundance of snail was atthe station III (6,55 ind/m2) and the lowest was at the station I (1,99 ind/m2).Statistical analysis (Anova) show that there was no significant differentabundance among those stations. Regression analysis show that the relationshipbetween the abundance of T. telescopium and organic sediment content wasnegatively correlated (r = 0,453).Keywords: Telescopium telescopium, abundance, organic Sediment, Dumai Riverestuary